EXPLORING PATIENT PERCEPTIONS OF BARRIERS AND FACILITATORS TO RECOVERY FOLLOWING TRAUMA. (7th October 2012) - Gabbe, B; Sleney, J; Gosling, C; Wilson, K; Sutherland, A; Hart, M; Watterson, D; Christie, N
Abstract : Background: The consequences of injury are many, resulting in diverse patient outcomes and recovery experiences. While disability is prevalent post-injury, 'why' and 'how' patient and system factors interact to impact on patient recovery is not known, and requires a qualitative study approach. Aims/Objectives/Purpose: The aims were to: (i) Explore the individual and societal impacts of trauma experienced by survivors of serious injury; and (ii) Provide evidence of the facilitators and barriers to recovery for trauma survivors. Methods: In-depth interviews of 120 hospitalised trauma patients were conducted. Participants were recruited from the Victorian Orthopaedic Trauma Outcomes Registry and the Victorian State Trauma Registry in Australia. Purposeful quota sampling was used to ensure a range of ages, and injury severity, with the intention to ensure equal representation by gender and compensation status. The interviews were recorded and transcribed to enable thematic content analysis. Results/Outcome: Most participants reported positive experiences with acute care with most negative experiences related to lack of coordination of post-discharge care, poor communication with health care providers, pain management issues and delays in accessing services. Many experienced some emotional impact from their injury, describing the experience as 'life changing'. Financial consequences were common, particularly for working age participants. Support of family and friends, and a resilient or positive attitude were considered the most important facilitators of recovery. Significance/Contribution to the Field: The narratives provided an unparalleled insight into the issues faced by injured participants as they recover, and provide valuable information for informing recommendations for improving trauma care.